Playing The Game: Ethnicity And Politics In Indonesian Badminton - Brown, Colin (Cornell University, Southeast Asia Program, 2006)
In only one sport does Indonesia excel at the international level: badminton. This paper focuses on three aspects of the sport: badminton’s role in shaping Indonesian nationalism and national identity; why the game had been so dominated by ethnic Chinese players; and the extent to which political leaders, and badminton players themselves, have used the game for political purposes.